2004
DOI: 10.1002/pmic.200300810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐fat diet on the expression of proteins in muscle, adipose tissues, and liver of C57BL/6 mice

Abstract: In the present study, the effect of a high fat diet on the expression of proteins in insulin target tissues was analyzed using a proteomic approach. Gastrocnemius muscle, white and brown adipose tissue, and liver were taken from C57BL/6 mice either fed on a high-fat or a chow diet. Expression levels of approximately 10 000 polypeptides for all the four tissues were assessed by two-dimensional gel electrophoresis (2-DE). Computer-assisted image analysis allowed the detection of 50 significantly (p < 0.05) diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 63 publications
(22 reference statements)
8
85
0
Order By: Relevance
“…In order to detect markers of high fat diet and insulin resistance Schmid et al performed an interesting 2DGE study (Schmid, et al 2004). Muscle, white and brown adipose tissue and liver were taken from normal mice fed a high fat or a normal chow diet.…”
Section: Protein Profiling Of Fat Muscle and Livermentioning
confidence: 99%
“…In order to detect markers of high fat diet and insulin resistance Schmid et al performed an interesting 2DGE study (Schmid, et al 2004). Muscle, white and brown adipose tissue and liver were taken from normal mice fed a high fat or a normal chow diet.…”
Section: Protein Profiling Of Fat Muscle and Livermentioning
confidence: 99%
“…ME1 promotes the release of acetyl-coenzyme A and NADPH from the mitochondria into the cytosol for de novo fatty acid biosynthesis. In addition, previous studies have indicated that MDH1, MDH2 and ME1 are associated with type II diabetes (Schmid et al, 2004;Zhong et al, 2010), and the synthesis and secretion of lipids (Bourneuf et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MDH1 and MDH2 are involved in de novo lipid synthesis by providing extramitochondrial reducing equivalents from the oxidation of malate (Schmid et al, 2004;Bourneuf et al, 2006). ME1 (malic enzyme), an NADP-dependent lipogenic enzyme, is involved in the conversion of L-malate to pyruvate.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no studies have been published on the adipose tissue secretome. Several studies investigated the human (10), mouse (11)(12)(13)(14), and rat (15) adipose tissue proteome, mostly using a two-dimensional gel electrophoresis approach. Celis et al (16) analyzed the human mammary adipose tissue proteome.…”
mentioning
confidence: 99%